The application of high-degree freedom titanium alloy implant based on TPMS in the repair of metacarpal bone defects - Mingrui Liu; Tao Lin; Jiaying Li; Junkai Hu; Lin Xu; Lincong Luo; Wenhua Huang (Materials & Design)
High design freedom is crucial for enhancing personalized manufacturing. Although extensive research has explored the relationship between lattice design, mechanical properties, and bone integration in 3D-printed implants, limited literature exists on their design and application in personalized implants. This study presents a novel biomedical design approach based on TPMS (Triply Periodic Minimal Surface) structures aimed at achieving target porosity, excellent biomechanical matching, and accelerated bone fusion to meet clinical demands for personalized treatment and reconstruction of defective bones. Using 3D structural optimization, a personalized biomimetic bone defect implant model (G model) based on Gyroid solid network structures was designed, with Ti-6Al-4V alloy as the material for 3D printing. The implant was comprehensively evaluated through mechanical testing, cytotoxicity, osteogenic differentiation experiments, and finite element analysis. Our results show that the G model exhibits excellent porosity, cellular compatibility, and mechanical strength. It can promote the expression of ALP and OPN genes at later stages, facilitating the repair of metacarpal bone defects. Compared to traditional surgical methods (E structure), it shows greater potential in restoring metacarpal function. This personalized design framework can be applied to other bone graft devices that require custom mechanical properties and bone integration performance, with significant clinical application potential.